Estimation of the Breeding Values and Genetic Parameters in Teleorman Black Head Sheep Breed - Florin Popa; Horia Grosu; Mircea Catalin Rotar; Rodica Stefania Pelmus; Mihail Alexandru Gras; Cristina Lazar (Scientific Papers Animal Science and Biotechnologies, 2023)
The aim of this paper was to study the breeding values and genetic parameters estimation methodology applied on Teleorman Black Head Sheep breed genetic improvement programs. Throughout study were estimated heritability using test-day milk yield and the genetic correlation between test-days milk yield for Teleorman Black Head Sheep from Dobrotești Teleorman area. The genetic parameters of daily milk yield during one lactation of Teleorman Black Head ewes were estimated with random regression test-day animal model. Data consisted of 1032 test-day records from 344 ewes. The breeding values for test day milk yield for the best ewes were ranged between 14.57 g milk and 28.48 g milk. The heritability estimates for three test-day milk yield of ewes were: 0.105 for first test day record, 0.270 for second test day record and 0.250 for third test day record. Genetic correlations between individual test days milk yield records were positive and of medium magnitude. Once again during the present research we observed that the test-day is the most appropriate methodology for milk production genetic evaluation in sheep, who offer the best improvement of the performances by genetic progress. That why random regression model was used the most in different countries, giving a better accuracy for breeding value, and ranking better the best ewes